THE INFLUENCE OF SHELLS DRAFT OF CRYSTALLIZER PAN ON ITS PERSISTENCE AND QUALITY OF THE CAST INGOT - A. V. Demin; O. M. Grudnitsky; A. V. Feklistov; A. I. Rozhkov; V. V. Nikolaev (Литьë и металлургия)
The effect of the crystallizers shells conicity on its durability and quality of the cast ingot. It is shown that the modification to change the conicity allowed to optimize the profile of copper shells to increase the quality of the bloom, increase productivity, continuous casting machine.